2001
DOI: 10.1080/02724930120077853
|View full text |Cite
|
Sign up to set email alerts
|

The Ibadan conjoined twins: a report of omphalopagus twins and a review of cases reported in Nigeria over 60 years

Abstract: An omphalopagus set of female conjoined twins, undiagnosed prenatally, who presented as obstructed labour needing operative delivery is reported. Their anatomic characteristics and clinical features, including overwhelming sepsis in twin II which forced early separation, and those which led to their demise are described. Twelve other cases reported in Nigeria over the past 60 years are reviewed with reference to the aetiology and epidemiology of conjoined twinning and the determinants of successful surgical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Review of available literature showed that 18 cases have been reported across the country in the last 76 years from 1935 to 2012. Five cases, 28%, were reported from a single center in the North, Zaria, 8 while the other cases were reported from Ibadan, 3 Ife, 9 Enugu 10 and few tertiary health centers in other parts of the country. The higher report from Zaria may be due to the heightened interest of the workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of available literature showed that 18 cases have been reported across the country in the last 76 years from 1935 to 2012. Five cases, 28%, were reported from a single center in the North, Zaria, 8 while the other cases were reported from Ibadan, 3 Ife, 9 Enugu 10 and few tertiary health centers in other parts of the country. The higher report from Zaria may be due to the heightened interest of the workers.…”
Section: Discussionmentioning
confidence: 99%
“…We report our experience with conjoined twins over a twelve year period in a tertiary hospital in Nigeria and a case of the first set of conjoined twin survivors in Benin City, Nigeria. The incidence of conjoined twins in Nigeria is unknown; however an article published in 2001 suggests that over the preceding 60 years there were 12 published cases nationwide, 3 excluding our own cases. The cases seen in our center have so far not been reported perhaps because this center had not recorded any survival of conjoined twins since its existence three and half decades ago.…”
Section: Introductionmentioning
confidence: 99%
“…This probably does not reflect the true incidence in Nigeria as most of the cases are not reported on account of the associated stigma. [4] Cases of conjoined twins seen in hospital are rare and pose a management challenge when they present because of paucity of experience in managing them. [4] The present case is of interest because of its extreme rarity, and the fact that it is the first such dicephalus dipud type to have been managed in our centre.…”
Section: Introductionmentioning
confidence: 99%
“…The above strategy, applied also to other malformations, gives better chances for favourable treatment outcomes. It eliminates iatrogenic effects of prolonged transportation on the child's health condition and enables proper preparation of the specialist centre [5]. It should be however borne in mind that Siamese twins are such a complicated developmental defect that even the use of the most advanced diagnostic methods does not always allow to assess accurately the configuration of twins' internal organs, hence final verification is possible only on the operating table [19].…”
mentioning
confidence: 99%
“…The majority of Siamese twins are stillborn or die shortly after birth due to accompanying developmental defects, hence they constitute an extremely small group of patients. The defect is three times more frequent in girls [1][2][3][4][5][6]. Its occurrence has been found to vary significantly by geographical region and race.…”
mentioning
confidence: 99%